Upregulated Expression of Integrin α1 in Mesangial Cells and Integrin α3 and Vimentin in Podocytes of Col4a3-Null (Alport) Mice - Steenhard, Brooke M.; Vanacore, Roberto; Friedman, David; Zelenchuk, Adrian; Stroganova, Larysa; Isom, Kathryn; St. John, Patricia L.; Hudson, Billy G.; Abrahamson, Dale R. (PLOS ONE, 2012)
Alport disease in humans, which usually results in proteinuria and kidney failure, is caused by mutations to the COL4A3, COL4A4, or COL4A5 genes, and absence of collagen α3α4α5(IV) networks found in mature kidney glomerular basement membrane (GBM). The Alport mouse harbors a deletion of the Col4a3 gene, which also results in the lack of GBM collagen α3α4α5(IV). This animal model shares many features with human Alport patients, including the retention of collagen α1α2α1(IV) in GBMs, effacement of podocyte foot processes, gradual loss of glomerular barrier properties, and progression to renal failure. To learn more about the pathogenesis of Alport disease, we undertook a discovery proteomics approach to identify proteins that were differentially expressed in glomeruli purified from Alport and wild-type mouse kidneys. Pairs of cy3- and cy5-labeled extracts from 5-week old Alport and wild-type glomeruli, respectively, underwent 2-dimensional difference gel electrophoresis. Differentially expressed proteins were digested with trypsin and prepared for mass spectrometry, peptide ion mapping/fingerprinting, and protein identification through database searching. The intermediate filament protein, vimentin, was upregulated ∼2.5 fold in Alport glomeruli compared to wild-type. Upregulation was confirmed by quantitative real time RT-PCR of isolated Alport glomeruli (5.4 fold over wild-type), and quantitative confocal immunofluorescence microscopy localized over-expressed vimentin specifically to Alport podocytes. We next hypothesized that increases in vimentin abundance might affect the basement membrane protein receptors, integrins, and screened Alport and wild-type glomeruli for expression of integrins likely to be the main receptors for GBM type IV collagen and laminin. Quantitative immunofluorescence showed an increase in integrin α1 expression in Alport mesangial cells and an increase in integrin α3 in Alport podocytes. We conclude that overexpression of mesangial integrin α1 and podocyte vimentin and integrin α3 may be important features of glomerular Alport disease, possibly affecting cell-signaling, cell shape and cellular adhesion to the GBM.